Role of radiotherapy in heterotopic ossification: a case report and literature review - Huang, Ming-Shan; Chen, Yu-Hsuan; Kuo, Sung-Hsin (Therapeutic Radiology and Oncology, 2018)
Heterotopic ossification (HO), a process of pathological bone formation in non-osseous tissue limits range of motion and causes stiffness of the affected joints. In addition to the administration of non-steroidal anti-inflammatory drugs, radiotherapy (RT) serves as an alternative prophylactic modality for the management of HO because RT potentially inhibits osteoprogenitor cell proliferation. We report a case of a 52-year-old woman with known underlying medical conditions who developed grade 4 HO at her left hip joint following a cerebrovascular accident. She then underwent RT using conventional opposed anterior-posterior configurations to the left hip joint at a dose of 10 Gray (Gy) delivered in 2 fractions on 2 consecutive days, within 48 hours after excision of the HO. The patient did not report any acute adverse effects related to RT and demonstrated clinical improvement in her range of motion at the left hip without any recurrence of HO at her 2-year follow-up. Although HO is a rare disease entity, our results and those of prior studies demonstrate that the administration of RT using a 10 Gy dose delivered in 2 fractions postoperatively is a safe and effective prophylactic treatment option against HO.